Didymocarpus heucherifolius var. yinzhengii (Gesneriaceae), a new taxon from Hunan, China - Li, Jiamei; Li, Shijin (Phytotaxa, 2014)
Didymocarpus heucherifolius var. yinzhengii from Hunan, China, is described and illustrated here. It is most closely related to the more widespread D. heucherifolius heucherifolius which shares calyx decided to the base and a number of similar vegetative characters. However, the new taxon is readily distinguished from the letter by the following: larger flowers (corolla up to 4cm long), corolla glabrous outside, puberulent inside at the base and staminodes absent.